The Role of Leadership, Organizational Commitment, and Motivation on Employee Performance - Herty Ramayanti Sinaga; Yuviani Kusumawardhani; Rahayu Sri Purnami (Sanskara Manajemen Dan Bisnis, 2026)
This study examines the effects of leadership, organizational commitment, and work motivation on employee performance. An explanatory quantitative approach was employed, involving 120 employees as respondents. Primary data were collected through a structured questionnaire and analyzed using IBM SPSS Statistics. Prior to regression analysis, the research instrument was assessed through validity and reliability testing, followed by classical assumption tests. The results indicate that leadership, organizational commitment, and work motivation have positive and significant effects on employee performance, both partially and simultaneously. Work motivation emerged as the strongest predictor in the model. These findings underscore the importance of effective leadership, employees’ attachment to the organization, and motivational conditions that support performance achievement.